Signal-on electrochemical DNA (E-DNA) sensor for accurate quantification of nicking-assisted rolling circle amplification (N-RCA) products with attomolar sensitivity. Issue 46 (23rd November 2021) - Li, Mengmeng; Li, Dandan; Huang, Guidan; Zhou, Linying; Wen, Qilin; Zhu, Wenyuan; Pan, Hongcheng
Abstract : A signal-on E-DNA sensor was developed for accurate quantification of N-RCA products with high specificity and sensitivity. Abstract : Rolling circle amplification (RCA) has become an increasingly important amplification technique in nucleic acid analysis, immunoassay, and molecular diagnosis due to its high specificity and sensitivity. However, the accurate quantification of RCA products via the extensively used fluorescent signaling method has been challenged primarily by the non-specific and sequence-independent binding of the fluorescent dyes to DNA. Here, we have developed a signal-on E-DNA sensor for accurate quantification of the RCA products with high specificity and sensitivity. A restriction enzyme was introduced to cleave the long tandem repeat sequences generated in the RCA reaction into many short monomers. The short monomers were then used as secondary targets to trigger the E-DNA sensor to produce an amplified redox current and thus the resulting RCA products were detected. The method was successfully applied to the detection of miR-7a with high specificity and the detection limit was as low as 0.59 fM.